Cardanol isolated from Thai Apis mellifera propolis induces cell cycle arrest and apoptosis of BT-474 breast cancer cells via p21 upregulation. Issue 1 (December 2015) - Buahorm, Sureerat; Puthong, Songchan; Palaga, Tanapat; Lirdprapamongkol, Kriengsak; Phuwapraisirisan, Preecha; Svasti, Jisnuson; Chanchao, Chanpen
Abstract Background Cardanol was previously reported to be an antiproliferative compound purified from ThaiApis mellifera propolis. By morphology, it could induce the cell death to many cancer cell lines but not the control (non-transformed human foreskin fibroblast cell line, Hs27). Here, it was aimed to evaluate the molecular effects of cardanol on breast cancer derived cell line (BT-474). Methods Morphological changes in BT-474 cells induced by cardanol compared to doxorubicin were evaluated by light microscopy, cytotoxicity by using the 3- (4, 5-dimethyl-thiazol-2-yl) 2, 5-diphenyl-tetrazolium bromide (MTT) assay, induction of cell cycle arrest and cell death by flow cytometric analysis of propidium iodide and annexin-V stained cells, and changes in the expression level of genes involved in the control of apoptosis and the cell cycle by quantitative reverse transcriptase-PCR (qRT-PCR) and western blot analyses. Results It revealed that cardanol induced a time- and dose-dependent cytotoxicity along with cell shrinkage and detachment from substratum. Cardanol caused cell cycle arrest at the G1 subphase (as opposed to at the G2 /M subphase seen with doxorubicin) and cell death by late apoptosis, with both late apoptosis (27.2 ± 1.1 %) and necrosis (25.4 ± 1.4 %) being found in cardanol treated cells after 72 h, compared to a lower proportion of apoptosis (4.3 ± 0.4 %) and higher proportion of necrosis (35.8 ± 13.0 %) induced by doxorubicin. Moreover, cardanol changed the transcript expression levels of genes involved in the control of apoptosis (increasedDR5 andBcl-2 expression and decreasedMcl-1, MADD andc-FLIPP ) and cell division (increased p21 and E2FI and decreased cyclin D1, cyclin E, CDK4 and CDK2 expression), as well as increasing the level of p21 p-ERK, p-JNK and p-p38 and decreasing cyclin D. This accounts for the failure to progress from the G1 to the S subphase. Conclusion Cardanol is a potential chemotherapeutic agent for breast cancer.